Liposomes: A Comprehensive Review on Development & Evaluation Parameters - Pandey, Garima; Negi, Anjali (Journal of Neonatal Surgery, 2025)
Liposomes were the first nanomedicine to receive authorisation for clinical use. Liposomes' remarkable ability to stop drug deterioration and reduce undesirable side effects has led to an increase in their application for targeted drug administration. Drugs in liposomes can either be incorporated into the phospholipid bilayer (hydrophobic drugs) or the aqueous space (hydrophilic drugs). The primary topics explored in this study are liposome classification, liposome production, utilises and their benefits and limitations. Nowadays, liposomes have captured the keen interest of most researchers. Because they are uncomplicated to create, effective against a particular ailment, and offer a number of extra advantages over others. This review discussed the current state, limitations, and uses of liposomes as a modified dosage form. Because liposomes work well as therapeutic agents, many formulations based on liposomes with increased drug concentrations have been created